Infrastructure for sustainable use of animal genetic resources in southern and eastern Africa - Zonabend König, Emelie; Okeyo Mwai, Ally; Ojango, Julie M.K.; Hoffmann, I.; Moyo, Siboniso; Philipsson, J. (Cambridge University Press, 2013)
The Global Plan of Action (GPA) for Animal Genetic Resources (AnGR) adopted by FAO recognizes the role of AnGR for food security through improved productivity while maintaining genetic diversity. A critical issue for conservation and genetic improvement programmes is the availability of supportive infrastructure. The objective of the present study was to assess existing and needed infrastructure for sustainable use of AnGR in a sample of countries in Southern and Eastern Africa. Information was primarily obtained from semi-structured interviews with key personnel in animal breeding during country visits. Countries studied are at different stages of development. No complete breeding programmes are in place but some conservation programmes exist in most countries. Except for a few cases, livestock recording as basis for R&D and breeding practice is lacking. The institutional setup to support animal breeding programmes is fragmented and needs to be better integrated. Shortage of skilled personnel is noted as the most serious constraint for development. Countries with least university training in animal breeding have least developed AnGR activities. However, since the GPA was agreed upon, many countries have re-casted their policies and make efforts to develop breeding policies. A change in mindsets aiming at closer collaboration among institutions, farmer involvement and capacity development and strengthening at all levels is suggested.